Conserved Ecological Responses to Novel Urban Stressors - Anthony A. Snead; Emerald Lin; Shira Linsk; Lena Olson; Kristin M. Winchell (Journal of Biogeography, 2025)
Aim As anthropogenic activities continue, species are exposed to climate change and rapid urbanisation that alter their distribution; however, the relative contributions of climate and anthropogenic influence on species distribution are unknown for most species. We use an environmentally sensitive salamander genus ( Eurycea ) that occupies urban and forested habitats to test the relative importance of temperature‐, precipitation‐ and urbanisation‐related variables before placing these results into a phylogenetic context. We aim to test the impact of climate and urbanisation in driving the distribution of the genus while evaluating patterns of niche conservatism. Location Nearctic. Taxon Eurycea (Plethodontidae, Lungless Salamanders). Methods We developed MAXENT niche models for 13 Eurycea species using bioclimatic and urbanisation‐related variables. We assessed the importance of these environmental variables through permutation importance and compared response curves to determine niche overlap. Phylogenetic analyses tested for evolutionary constraints on species responses to environmental factors. Results Climatic variables were the primary drivers of Eurycea distributions, while urbanisation‐related variables had lower overall importance. Phylogenetic analyses revealed that responses to urbanisation‐related factors, specifically impervious surface and human population density, exhibited significant phylogenetic signal, indicating a stronger evolutionary constraint on responses to urbanisation than to climate. While climatic variables showed limited phylogenetic conservatism, niche overlap analyses demonstrated that more closely related species had greater similarity in ecological responses to urbanisation than to climate. Evolutionary history influenced species' ecological tolerances, with some environmental responses more conserved than expected under Brownian motion. Main Conclusions Our findings highlight the role of evolutionary history in shaping Eurycea responses to environmental variation. While climatic factors predominantly influence broadscale distributions, urbanisation‐related responses are more evolutionarily conserved across the genus. These results suggest that past evolutionary trajectories may constrain species' capacity to adapt to novel anthropogenic stressors, underscoring the importance of incorporating phylogenetic perspectives in conservation strategies for Eurycea and other evolutionarily constrained taxa.